(untitled) (Revista Electrónica REDINE, 2025)
Agroecological tourism stands out for promoting activities linked to organic farming, local food production and the preservation of rural landscapes. In this sense, this article seeks to promote sustainable agroecological tourism through the implementation of environmental interpretation strategies and the development of green infrastructures in the Ezequiel Zamora Botanical Garden (JBEZ). The methodology used is based on a qualitative descriptive field approach, supported by three stages of participatory action research. In-depth interviews were carried out with three visitors who took the "Lung Vegetal" agroecological tourist route. To analyze the information collected, tools such as categorization, triangulation, theorizing and contrasting were used. The diagnosis was used through a SWOT matrix, determining strengths, weaknesses, opportunities and threats. Successively, the routes were illustrated after the identification of the natural, cultural and agroecgological attractions. Finally, strategies were proposed to promote agroecological tourism in the Ezequiel Zamora Botanical Garden. In conclusion, the potential of JBEZ to position itself as a tourist destination of excellence in the region through a sustainable and responsible agroecological tourism approach is highlighted. The proper implementation of the strategies, together with the use of its strengths and opportunities, will allow JBEZ to be consolidated as a benchmark in nature tourism and agroecology.